Химия и технология урана: конспект лекций - Маслов А. А. Александр Антонович; Каляцкая Г. В. Галина Васильевна; Амелина Г. Н. Галина Николаевна; Водянкин А. Ю. Алексей Юрьевич; Егоров Н. Б. Николай Борисович (Томск, Изд-во ТПУ, 2003)
В фонде НТБ ТПУ отсутствует